Diagnostics of gas turbine systems using gas path analysis and rotordynamic response approach - Jombo, Gbanaibolou; Sampath, Suresh; Gray, Iain (ISABE, 2017)
The modern gas turbine is plagued with issues centred on improving engine availability and limiting component degradation. The integrated use of different condition monitoring techniques presents a solution to addressing these challenges. This paper lays a foundation for the integration of gas path analysis and the rotordynamic response of the compressor to monitor the effect of fouling in the compressor. In investigating the resultant interaction between the aerodynamic and rotordynamic domain in a compressor caused by fouling, an approach involving the interaction of four different models is explored. The first model, a gas turbine engine performance model is used to simulate a fouled compressor and quantify the extent of performance deterioration with gas path analysis. The extent of performance deterioration from the engine performance model represented by scaling of the compressor maps becomes an input in the second model, a Moore-Greitzer compression system model, which evaluates the disturbed flow field parameters in the fouled compressor. The third model, a momentum-based aerodynamic force model, predicts the fouling induced aerodynamic force based on the disturbed flow field parameters. The aerodynamic force acting as a forcing function in the fourth model, a compressor rotordynamic model, produces the vibration response. From the investigation carried out in this work, it is observed, as the rate of fouling increases in the compressor, typified by a decrease in compressor massflow, pressure ratio and isentropic efficiency, there is a corresponding increase in the vibration amplitude at the first fundamental frequency of the compressor.
Keywords: Moore-Greitzer Model; Compressor Fouling; GPA